THE ANALYSIS OF PRODUCTION CAPACITY USING ROUGH CUT CAPACITY PLANNING METHOD (CASE STUDY AT PT. UNTUK INDONESIA HIJAU): Analisis Kapasitas Produksi Menggunakan Metode Perencanaan Kapasitas Kasar (Studi Kasus di PT. Untuk Indonesia Hijau) - Hidayat, Amri; Achmad, Mahmud; Munira (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2025)
PT. Untuk Indonesia Hijau is a small-scale company based in Indonesia, specializing in the processing of cocoa beans to produce fermented cocoa beans, cocoa mass, and chocolate bars. Currently, the company's production process is driven by customer demand, often neglecting the efficient utilization of available facilities and resources, resulting in escalated operational costs. The existing workstations exhibit underutilized resources while certain machines and workers are overloaded in specific conditions. The objective of this study is to thoroughly evaluate and analysis the production capacity of each workstation for the production of each product. This comprehensive evaluation and analysis, employing the Rough-Cut Capacity Planning method, encompasses production forecasting, calculation of available capacity at each workstation, determination of the required capacity for each workstation, and a rigorous capacity feasibility test by comparing available capacity with required capacity. The findings of the Rough-Cut Capacity Planning using the CPOF method indicate that nearly all workstations demonstrate positive capacity values over 12 months, indicating that available capacity can satisfy production demands. However, there exists a considerable excess work capacity, underscoring the need for additional strategies to optimize operation efficiency